The universe is expanding by entirely moving at some very high speed and not by flying away of the galaxies from each other - Abunaieb, Salah (International Journal of Advanced Astronomy, 2015)
Expansion of the universe has already been confirmed by the Hubble discovered nebular red-shift. But, is it expanding in the simple Newtonian way that the distance between any observed distant star and the observer is continuously increasing? The argument against this is: If so, then the apparent brightness and size of that distant star will continuously decrease and thus the stars at the outer edge of the visible universe will disappear in no time. To understand the way in which the universe is expanding it is important, in accordance with the special theory of relativity, to bear in mind the fundamental difference between the way electromagnetic waves spread and the way Newtonian point particles move. Accordingly, the Hubble discovered nebular red-shift is explained here as due to relative motion between the Newtonian point particle observer, which is moving along with the entire universe, and the space-time fixed origins (Events) of the received pulses of light. But, as the source is also moving with the entire universe, these space-time fixed origins are continuously repeated on the continuous world line of the star and hence the recession is continuously repeated while the star remains at the same fixed distance from the observer.